Hypouricemia in Behçet's Syndrome: Prevalence and Clinical Outcomes - Oz, Burak; Gunduz, Ibrahim; Karatas, Ahmet; Koca, Suleyman S. (Mdpi, 2025)
Background and Objectives: Beh & ccedil;et's syndrome (BS) is a systemic inflammatory disorder characterized by recurrent oral and genital ulcers, uveitis, and vascular involvement. Serum uric acid (SUA) has been implicated in various inflammatory conditions, due to its antioxidant properties and role in oxidative stress. Abnormal SUA levels, particularly hypouricemia, may influence inflammatory processes, but their significance in BS pathophysiology remains unexplored. This study aimed to determine the prevalence of abnormal SUA levels among BS patients and investigate their associations with its clinical manifestations and laboratory parameters. Materials and Methods: A retrospective analysis was conducted on 436 patients with complete data who met the international criteria for Beh & ccedil;et's syndrome, including 420 patients classified as hypouricemic or normouricemic, for detailed evaluation. Patients were classified as hypouricemic (<3 mg/dL), hyperuricemic (>7 mg/dL), or normouricemic (3-7 mg/dL). Data on sociodemographics, laboratory findings, and clinical characteristics were collected. Mortality and malignancy associations were analyzed using logistic regression. Inverse probability weighting (IPW) was employed to adjust for confounding factors. Results: Initial unadjusted analysis showed that hypouricemic BS patients had significantly lower rates of acneiform lesions (7.3% vs. 14.4%, p = 0.020) and vascular involvement (3.8% vs. 11.6%, p = 0.038) compared to normouricemic patients. However, after adjustment for confounding variables using the IPW methodology, these associations lost statistical significance (p = 0.592 and p = 0.519, respectively). Both before and after adjustment, no significant differences were observed between groups regarding major organ involvement, disease severity, or activity markers. Conclusions: After controlling for confounding factors, hypouricemia in BS patients did not demonstrate significant associations with specific clinical manifestations or disease outcomes. While the unadjusted data initially suggested potential relationships with acneiform lesions and vascular involvement, these associations were not supported by comprehensive statistical analysis. Further prospective studies are warranted to elucidate the complex relationship between uric acid metabolism and BS pathophysiology.
Keywords: Beh & ccedil;et's syndrome; uric acid; hypouricemia; mortality